Analysis Of The Role Of Physical Education In The Management Of Clean And Healthy Living Behavior In Junior High School - Heru Kuswantono; Donny Setiawan; Wawan Setiawan (Journal Management of Sport, 2024)
One important factor that can affect the quality of human resources in supporting the development of a country is the health status of the community. This research uses descriptive qualitative method by describing or describing a social symptom, in other words, this research aims to describe something that is ongoing at the time of the study. The results showed that the lifestyle in class VIII students of SMP N 7 Jember is quite high in understanding clean and healthy living behaviour; lifestyle towards personal hygiene is quite high; lifestyle towards environmental hygiene is quite high; lifestyle towards illness and disease is less high; and lifestyle towards habits that damage Jember's health is quite high.